ESWL EFFICACY FOR VARIOUS DENSITY STONES (HU) ON PLAIN CT SCAN - REHMAN, AU; ULLAH, S; HAIDER, SF; SAJJAD, A (Biological and Clinical Sciences Research Journal, 2024)
Extracorporeal Shock Wave Lithotripsy (ESWL) is a keystone in the harmless management of urinary tract stones, offering a viable alternative to surgical mediation for patients pained by urolithiasis. Objectives: The study aims to find the ESWL efficacy for various density stones (HU) on plain CT scans. Methods: This observational study was conducted at CMH Lahore from February 17, 2024, to May 16, 2024. Data were collected from 180 patients suffering from renal stones. Males represented 60% (108 patients), while females 40% (72 patients). Predominantly, stones were located in the renal pelvis (45%), followed by the upper ureter (30%) and lower ureter (25%). The mean stone size was 10 mm, ranging from 5 to 20 mm, with a corresponding mean stone density of 900 Hounsfield Units (HU) as measured on Plain CT Scan. Results: Data were collected from 180 patients. The mean age of the patients was 50.98±2.34 years. There were 60% male and 40% female patients. According to stone location, 45% are located at the renal pelvis, 30 at the upper ureter and 25% at the lower ureter. A mean reduction in the stone size of 65% post-treatment underscores the procedure's ability to facilitate stone disintegration. Stone-free rates varied based on stone density, with higher rates observed for stones with lower densities: 85% for stones ≤ 700 HU, 75% for stones > 700 HU and ≤ 1000 HU, and 65% for stones > 1000 HU. Conclusion: It is concluded that an accurate assessment of stone density and ESWL score is vital in directing treatment decisions and upgrading outcomes for patients going through ESWL for urinary stones. These findings highlight the importance of personalised treatment approaches and the potential of the ESWL score as an essential tool in clinical practice.